Are there future psychiatrists among medical students in Croatia? The role of premedical and medical factors on career choice in psychiatry. (August 2013) - Rojnic Kuzman, Martina; Smoljan, Mia; Lovrec, Petra; Jovanovic, Nikolina; Lydall, Greg; Farooq, Kitty; Malik, Amit; Bhugra, Dinesh
Abstract Despite the high prevalence of mental disorders, a worldwide shortage of psychiatrists exists. Moreover, the number of students interested in choosing psychiatry as their future profession is low and psychiatry is frequently regarded as one of the least wanted medical specializations. We report the findings of a cross-sectional quantitative survey of final year Croatian medical students as part of the International Survey of Student Career Choice in Psychiatry (ISoSCCiP). The questionnaire consisted of three sections: socio-demographic factors, psychiatric education during medical school, and attitudes and personality characteristics. Out of 200 students, 122 completed the questionnaire (response rate 61%). The overall student evaluation of the compulsory psychiatry curriculum was 'average'. Significantly higher ratings were reported by students who attended special psychiatry teaching modules, or felt more involved in the teaching of the subject. Poor evaluation of medical school psychiatric education significantly increased the likelihood of not choosing psychiatry as a future career. The choice of psychiatry was also predicted by attitudes towards psychiatry and by personal characteristics. In conclusion, student ratings of medical school psychiatric education and involvement in teaching appear to influence choice towards psychiatry. Addressing these issues may increase the number of students motivated to pursue psychiatry as their future career choice.